G299(P) Antibiotic usage and chest radiography in children admitted for community acquired pneumonia. (25th October 2020) - Round, AC; Ng, KF; Vasudeva, D; Manzoor, N; Radcliffe, R; Lo, D; Koo, S
Abstract : Aims: To audit the antibiotic choice, route of administration, and duration of treatment; as well as frequency of, and indication for, chest radiographs among children admitted for CAP. Methods: A retrospective audit was conducted on patients aged 0–18 who were admitted with a diagnosis of CAP between December 2018 and February 2019. Patients were identified by International Statistical Classification of Diseases and Related Health Problems (ICD) discharge coding. Data were collected from 50 patients' case notes and electronic notes. Results: Chest x-ray: The median number of CXR performed was 1. Performance of more than one CXR occurred in 32% (16/50) of children, 31% (5/16) of whom did not require oxygen supplementation or PICU admission. Antibiotic usage: Antibiotic choice : Amoxicillin was prescribed as the first line antibiotic for 13% (6/48) of children admitted with CAP. Instead, 56% (27/50) were started on cefuroxime, 10% (5/48) co-amoxiclav, 8% (4/48) ceftriaxone and 13% (6/48) on other antibiotics. A combination of 2 or more antibiotics were given to 55% (26/48) of patients; 19% of which had no documented reason found. The decision to prescribe multiple antibiotics was not associated with age, presence of co-morbidity, oxygen requirement, PICU admission, length of hospitalisation or antibiotic duration. Antibiotic route : IV antibiotics were started in 81% (39/48) of children, with no documented justification of this decision in 26% (10/39) of cases. The presence of co-morbidity and oxygen requirement were not statistically associated with antibiotic route of administration. Antibiotic duration: The median duration of antibiotics was 7 days (range 1–67 days). Conclusions: Our audit suggests there was excessive usage of broad-spectrum antibiotics for the treatment of inpatient paediatric CAP; contrary to BTS standards recommending amoxicillin as first line antibiotic choice. Following BTS standards recommending that oral antibiotics are effective even in severe CAP and the lack of association between oxygen requirement and antibiotic route, we suspect that the proportion of children started on oral antibiotic for CAP should have been higher. There is a need to improve CAP management in children, particularly regarding antibiotic choice and route of administration as well as reducing the number of unnecessary CXR performed on children admitted for CAP.